ASSOCIATION BETWEEN DIETARY HABITS AND PREHYPERTENSION AMONG INDONESIAN YOUNG ADULTS AT PROF. DR. R. D. KANDOU HOSPITAL MANADO - Wowor, Ribka (JURNAL BIOMEDIK : JBM, 2019)
Abstract: Prehypertension is a warning sign, early in age which denotes the risk of hypertension later on in life. Clinical and academic challenges of medical students may have adverse effect on their lifestyle, predisposing vulnerable subjects to elevated blood pressure. This study was aimed to determine the association between dietary habits and prehypertension among Indonesian young adults in Manado. This was an analytical study with a cross-sectional study. Subjects were 111 medical students (undergraduate and postgraduate) aged between 20-30 years, of either sex. A pre-tested questionnaire was used to elicit the details on physical activity, family history of hypertension, tobacco use, and dietary habits. According to JNC-7 guidelines, a systolic blood pressure (SBP) of 120 to 139 mmHg and/or diastolic blood pressure (DBP) of 80 to 89 mmHg is considered as prehypertension. Of the 111 subjects, 22.5% showed blood pressure levels within the range of prehypertension. Chi-square analysis revealed that junk food consumption (OR=3,152; 95% CI=1,253-7,925; P=0,023), and soft drink consumption (OR=4,747; 95% CI=1,797-12,539; P=0,002) were the risk factors of prehypertension. Conclusion: Dietary habits were associated with the prehypertension among young adults in Manado.Keywords: dietary habits, prehypertension, young adultsAbstrak: Prehipertensi merupakan tanda peringatan dini akan resiko terjadinya hipertensi di kemudian hari. Mahasiswa kedokteran memiliki kesibukan studi terutama pada masa kepaniteraan klinik di Rumah Sakit. Tuntutan dalam pendidikan dan pelayanan sekaligus di RS berdampak terhadap pola aktivitas mereka sehari-hari sehingga dapat memengaruhi tekanan darah. Penelitian ini bertujuan untuk mengetahui hubungan antara diet (konsumsi makanan dan minuman) dengan kejadian prehipertensi pada mahasiswa kedokteran Univrsitas Sam Ratulangi. Jenis penelitian ialah analitik dengan desain potong lintang. Hasil penelitian mendapatkan 111 mahasiswa kedokteran peserta P3D dan PPDS (calon spesialis) berusia antara 20-30 tahun sebagai subyek penelitian. Dilakukan pemeriksaan tekanan darah dan berat badan. Penentuan kebiasaan makan ditetapkan berdasarkan hasil pengisian kuesioner. Definisi prehipertensi berdasarkan kriteria JNC 7 yaitu tekanan darah sistolik lebih dari 120 mmHg tapi kurang dari 140 mmHg, dan atau tekanan darah diastolik lebih dari 80 mmHg tapi kurang dari 90 mmHg. Uji Chi-square dilakukan untuk melihat hubungan antara konsumsi junk food dan soft drink dengan kejadian prehipertensi dan didapatkan adanya hubungan antara konsumsi junk food (OR=3,152; 95% CI=1,253-7,925; P=0,023), dan soft drink (OR=4,747; 95% CI=1,797-12,539; P=0,002) dengan kejadian prehipertensi pada subyek dewasa muda. Simpulan: Diet (konsumsi junk food dan soft drink) berhubungan dengan kejadian prehipertensi pada subyek dewasa muda di Manado.Kata kunci: diet, prehipertensi, dewasa muda